Addressing food insecurity in early childhood programs through a health equity lens: A qualitative case study of Brazil’s Criança Feliz program - Gabriela Buccini; Poliana de Araújo Palmeira; Ana Poblacion; Muriel Bauermann Gubert (PLoS ONE, 2025)
Background Food insecurity negatively impacts early childhood health and development. Recommendations for establishing equitable actions to address food insecurity in early childhood programming have not been developed globally. The Brazilian Criança Feliz Program (PCF), one of the largest early childhood programs worldwide, has faced implementation challenges while addressing food insecurity. We aimed to (i) understand how food insecurity affects the PCF’s internal (i.e., organizational-level factors) and external (i.e., family-level and system-level factors) implementation contexts, and (ii) develop equity-focused recommendations for early childhood programs to mitigate food insecurity. Methods Qualitative case study analyses of in-depth interviews with PCF implementation teams and families in five Brazilian municipalities. Participants shared their experience with PCF implementation quality, including questions related to food insecurity. A three-stage rapid qualitative approach was used: (a) inductive thematic analysis identified central codes related to food insecurity, (b) deductive approach to organize central codes within themes related to internal and external contexts of PCF operations, and (c) integration of findings into a set of equity-focused recommendations based on the four categories of the Getting to Equity (GTE) framework. Results 240 interviews were conducted. Internal programmatic barriers included lack of protocols for screening, referring, and following up with families struggling to access food as well as challenges to engage them in early learning activities. External programmatic barriers included family-level factors (e.g., unrealistic support expected from PCF) and system-level factors (e.g., bureaucracy in accessing safety nets). Ten equity-focused recommendations across GTE framework focused on improving program curriculum and protocols to mitigate food insecurity and increasing individual and community capacity. Conclusions We documented barriers at the family, program, and system levels to address food insecurity in the Brazilian PCF home visiting program. Barriers informed the generation of equity-focused programming recommendations to improve practices to address food insecurity, not only for the PCF, but also for the global community implementing home visiting programs.